The Decentralised Amanah Fund (DAF): An Islamic Ethical Fiscal Framework for Equitable Local Governance in the Maldives - Abdulhameed Husain; Abdulwahed Jalal Nori Nori; Ahmad El-Muhammady bin Muhammad Uthman El-Muhammady (Penerbit Hellow Pustaka, 2026)
This paper articulates the development of the Decentralised Amanah Fund (DAF) as an Islamic, ethics-oriented fiscal decentralisation model for the Republic of Maldives. Despite the Maldives’ commitment to decentralisation since the inception of the 2008 Constitution and the subsequent Decentralisation Act of 2010, fiscal authority remains predominantly centralised in Malé, leaving local councils reliant on politicised, inconsistent, or non-transparent allocations. Concurrently, several national welfare and fiscal instruments—including the Old-Age Basic Pension, the Maldives Retirement Pension Scheme (MRPS), the Sovereign Development Fund (SDF), the Public Sector Investment Programme (PSIP), and the universal health insurance initiative Aasandha—have been subjected to recurrent public scrutiny due to delays, ambiguous eligibility criteria, inadequate ethical accountability, and, in certain cases, onerous “pay-first-claim-later” practices that adversely affect vulnerable citizens. These challenges reveal what this paper identifies as an ethical deficit in fiscal governance: the formal existence of welfare schemes without the substantive actualisation of ʿadālah (justice), amānah (trust), and maṣlaḥah (public welfare). Drawing together (i) the economic and institutional logic of fiscal decentralisation in public finance (Musgrave, 1959; Oates, 1972; Faguet, 2014; Martinez-Vazquez & McNab, 2020) and (ii) Islamic governance ethics rooted in divine trusteeship, distributive justice, and consultative decision-making (Q 4:58; Q 4:135; Q 42:38; Kamali, 2021; Chapra, 2019; Ahmed & Asutay, 2022), the paper argues that decentralisation in a Muslim polity cannot be merely a technical or administrative project. It must embed dual accountability—to Allah and to citizens. The DAF is therefore proposed as a trust-based, rule-based, participatory, and transparently audited fiscal transfer mechanism in which local councils receive funds as amīn (trustees), not as passive spending agents. The model is enriched with comparative lessons from Indonesia’s Dana Desa, Malaysia’s integration of zakāt and waqf into development, Kenya’s county revenue-sharing formula, and Bangladesh’s performance-based local grants. The paper makes four contributions. First, it articulates DAF as the fiscal arm of Islamic decentralised governance for the Maldives, consistent with Article 10(a) of the Maldivian Constitution (2008) that situates Islam as the basis of all laws. Second, it shows—through two Maldivian illustrative cases, one on Aasandha and one on the Old-Age Basic Pension—how administrative and procedural barriers can contradict the original maṣlaḥah intent of national schemes, and how a DAF-style decentralised ethical audit would have corrected them. Third, it proposes a structured DAF Ethical Fiscal Loop that integrates allocation, shūrā-based budgeting, maṣlaḥah-oriented implementation, and a final musa’ālah (accountability) cycle. Fourth, it outlines a staged implementation roadmap—legal, institutional, technological, and educational—that enables Maldivian authorities to transition from centralised, opaque fiscalism to localised, ethical stewardship. The study concludes that institutionalising DAF would convert Maldivian decentralisation from “transferring tasks” to “transferring trust,” thereby advancing national development, social justice, and Islamic public morality at the same time.